2013
DOI: 10.1152/ajplung.00183.2013
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells in patients with chronic obstructive pulmonary disease

Abstract: The pathogenesis of chronic obstructive pulmonary disease is not fully understood. The objective of this study was to compare circulating endothelial progenitor cells in patients with chronic obstructive pulmonary disease to age, sex, and cigarette smoking matched healthy controls. Patients with chronic obstructive pulmonary disease (n = 37) and healthy controls (n = 19) were matched by age, sex, and smoking status. Circulating hematopoietic progenitor cells (CD34(+) or CD133(+) mononuclear cells) and endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…PASCHALAKI et al [118] reported that endothelial progenitor cells from smokers and COPD patients exhibit evidence of DNA damage and senescence and thus possess impaired repair function. However, others have reported decreased hematopoietic progenitors, but unchanged numbers of circulating endothelial progenitor cells in COPD patients [119,120]. Moreover, dysfunction of other potential progenitor cell types, such as mesenchymal stromal cells (MSCs), has been associated with reduced repair capacity in a murine post-pneumectomy model [121].…”
Section: Stem Cell Exhaustionmentioning
confidence: 99%
“…PASCHALAKI et al [118] reported that endothelial progenitor cells from smokers and COPD patients exhibit evidence of DNA damage and senescence and thus possess impaired repair function. However, others have reported decreased hematopoietic progenitors, but unchanged numbers of circulating endothelial progenitor cells in COPD patients [119,120]. Moreover, dysfunction of other potential progenitor cell types, such as mesenchymal stromal cells (MSCs), has been associated with reduced repair capacity in a murine post-pneumectomy model [121].…”
Section: Stem Cell Exhaustionmentioning
confidence: 99%
“…The EPC-CFU assay was originally discovered by Hill et al (41). Variation in these studies findings may be attributed to differences in smoking history and co-morbidities between the subject populations.…”
Section: Enumeration Of Epcs With Early Outgrowth Epccfus In Copdmentioning
confidence: 99%
“…(22,47). In this regard, adult stem cells are thought to represent a potential cell source for lung repair (14,24,81,106,109,130,133,168). Furthermore, 3-D scaffolds reseeded with lung progenitors and stem cells, with additional stimuli via growth factors and mechanical forces (simulating those in the native lung) have been shown to induce cellular differentiation and formation of anatomically appropriate lung tissue (122,166).…”
Section: Recellularization In Lung Bioengineeringmentioning
confidence: 99%